Therapeutic targeting of “undruggable” MYC - Llombart, Victor; Mansour, Marc R (EBioMedicine, 2022)
c-MYC controls global gene expression and regulates cell proliferation, cell differentiation, cell cycle, metabolism and apoptosis. According to some estimates, MYC is dysregulated in ≈70% of human cancers and strong evidence implicates aberrantly expressed MYC in both tumor initiation and maintenance. In vivo studies show that MYC inhibition elicits a prominent anti-proliferative effect and sustained tumor regression while any alteration on healthy tissue remains reversible. This opens an exploitable window for treatment that makes MYC one of the most appealing therapeutic targets for cancer drug development. This review describes the main functional and structural features of the protein structure of MYC and provides a general overview of the most relevant or recently identified interactors that modulate MYC oncogenic activity. This review also summarizes the different approaches aiming to abrogate MYC oncogenic function, with a particular focus on the prototype inhibitors designed for the direct and indirect targeting of MYC.